Never Never - Patterson, James, 1947-; Fox, Candice; Holmes, Federay (New York : Hachette Audio, 2017)
While her brother is under arrest in Sydney for a series of brutal murders, Detective Harriet Blue is sent out of town to investigate the disappearance of three young people in the middle of the Western Australian desert.
Keywords: Women detectives -- Fiction; Missing persons -- Investigation; Fiction; Murder -- Investigation; Fiction; Western Australia -- Fiction; Suspense fiction; Audiobooks